Innovation and entrepreneurship: A lexical analysis from international and Brazilian national scientific studies (2015-2019) (Research, Society and Development, 2021)
The present article aimed to present a systematic bibliographic review on entrepreneurship and innovation from scientific papers published in Brazilian and international journals between 2015 and 2019 from the perspective of lexical analysis. In methodological terms, the word innovation and entrepreneurship were first cataloged at national and international level for the years proposed and which counted, among its keywords, the words innovation and entrepreneurship. Forty national and international scientific studies were selected and then coded to perform a lexical analysis through the software IRaMuteq (Interface of R pou les Analyses Multidimensionnelles de Textes et de Questionnaires). The results reveal that the textual corpus was categorized into six clusters. Clusters 5 and 6 revealed a connection to each other, as did clusters 1 and 4. Thus, it was possible to identify connections between the words "innovation" and "entrepreneurship" as central elements to form the word network and it is interesting to highlight that the word "entrepreneur" is shown to be a branch of the word "innovation" and not of the word "entrepreneurship" as expected.